STUDY OF LARUNGAN TRADITION IN BENDAR VILLAGE, JUWANA DISTRICT, PATI DISTRICT, CENTRAL JAVA - Eka Nur Jannah; Sunarru Samsi Hariadi; Subejo Subejo (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
This research was arranged to analyze the Larungan traditional ceremony conducted by the community in Bendar Village, Juwana District, Pati Regency. The research method uses descriptive analytic method. Larungan is a traditional ceremony performed by fishermen as a form of gratitude to God Almighty. The Larungan traditional ceremony is held every year on Shawwal on the seventh day, but if on the seventh day coincides with the Sunday Wage, the implementation is carried out on the day before or after the Sunday Wage, because on Sunday the Wage had an accident during the Larungan traditional ceremony. So, the Larungan traditional ceremony is a tradition carried out by the coastal community in Bendar Village, Juwana District, Pati Regency, the majority of whom work as fishermen as a form of gratitude to God Almighty for the fortune that has been given in the form of abundance fish catched from the sea.